2023
DOI: 10.3390/polym15051226
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Wavelength Lasing with Orthogonal Circular Polarizations Generated in a Single Layer of a Polymer–Cholesteric Liquid Crystal Superstructure

Abstract: We investigate the laser emission from a polymer–cholesteric liquid crystal superstructure with coexisting opposite chiralities fabricated by refilling a right-handed polymeric scaffold with a left-handed cholesteric liquid crystalline material. The superstructure exhibits two photonic band gaps corresponding to the right- and left-circularly polarized light. By adding a suitable dye, dual-wavelength lasing with orthogonal circular polarizations is realized in this single-layer structure. The wavelength of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Various CLC materials and structures have thus been developed to implement tunable reflective colors in a varying degree of wavelength tunability by modulating the CLC pitch directly through temperature variations [ 1 , 2 ], light irradiation [ 3 , 4 , 5 ], and applied voltage [ 6 , 7 , 8 ], or indirectly through electrothermal [ 9 , 10 , 11 , 12 ], mechanical [ 13 , 14 ], and hydrodynamic [ 15 ] effects. Due to their uniqueness, CLCs have been extensively exploited or introduced for numerous applications, including in color filters [ 16 , 17 ], lasers [ 18 , 19 ], reflective displays [ 20 , 21 ], reflective polarizers [ 22 , 23 ], sensors [ 24 , 25 , 26 , 27 , 28 ], and smart windows [ 29 , 30 , 31 ]. However, as birefringence in CLCs is typically lower than 0.2 and only one of the two circularly polarized components of light can be reflected, a CLC bandgap is inherently limited to reflect unpolarized light colors within a narrow bandwidth with a reflectance R % less than 50%.…”
Section: Introductionmentioning
confidence: 99%
“…Various CLC materials and structures have thus been developed to implement tunable reflective colors in a varying degree of wavelength tunability by modulating the CLC pitch directly through temperature variations [ 1 , 2 ], light irradiation [ 3 , 4 , 5 ], and applied voltage [ 6 , 7 , 8 ], or indirectly through electrothermal [ 9 , 10 , 11 , 12 ], mechanical [ 13 , 14 ], and hydrodynamic [ 15 ] effects. Due to their uniqueness, CLCs have been extensively exploited or introduced for numerous applications, including in color filters [ 16 , 17 ], lasers [ 18 , 19 ], reflective displays [ 20 , 21 ], reflective polarizers [ 22 , 23 ], sensors [ 24 , 25 , 26 , 27 , 28 ], and smart windows [ 29 , 30 , 31 ]. However, as birefringence in CLCs is typically lower than 0.2 and only one of the two circularly polarized components of light can be reflected, a CLC bandgap is inherently limited to reflect unpolarized light colors within a narrow bandwidth with a reflectance R % less than 50%.…”
Section: Introductionmentioning
confidence: 99%
“…One of the very attractive control methods is tuning via an applied electric field; however, its full potential has not yet been achieved [ 19 ]. Recently, several approaches to achieve lasing at different wavelengths have been demonstrated using a CLC multilayer system [ 20 ], emulsified polymer-dispersed liquid crystals (PDLCs) [ 21 ], CLC spherical micro-shells [ 22 ], and a defect mode laser structure [ 23 ] and topological lasing [ 24 ]. For instance, Barberi et al demonstrated multi-wavelength lasing through a combination of a photoluminescent dye layer and three cholesteric layers [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Barberi et al demonstrated multi-wavelength lasing through a combination of a photoluminescent dye layer and three cholesteric layers [ 20 ]. Multi-wavelength lasing from a polymer–cholesteric liquid crystal superstructure with coexisting opposite chiralities was also obtained by refilling a right-handed polymeric scaffold with a left-handed cholesteric liquid crystal material [ 23 ]. In addition, robust topological interface state lasing at multiple wavelengths of the visible spectrum in a micron-sized polymer-cholesteric liquid crystal superlattice was also demonstrated [ 24 ].…”
Section: Introductionmentioning
confidence: 99%